Processing of visual signals related to self-motion in the cerebellum of pigeons - Wylie, Douglas R. (Frontiers in Behavioral Neuroscience, 2013)
In this paper I describe the key features of optic flow processing in pigeons. Optic flow is the visual motion that occurs across the entire retina as a result of self-motion and is processed by subcortical visual pathways that project to the cerebellum. These pathways originate in two retinal-recipient nuclei, the nucleus of the basal optic root and the nucleus lentiformis mesencephali, which project to the vestibulocerebellum (folia IXcd and X), directly as mossy fibres, and indirectly as climbing fibres from the inferior olive. Optic flow information is integrated with vestibular input in the vestibulocerebellum. There is a clear separation of function in the vestibulocerebellum: Purkinje cells in the flocculus process optic flow resulting from self-rotation, whereas Purkinje cells in the uvula/nodulus process optic flow resulting from self-translation. Furthermore, Purkinje cells with particular optic flow preferences are organized topographically into parasagittal “zones”. These zones are correlated with expression of the isoenzyme aldolase C, also known as zebrin II (ZII). ZII expression is heterogeneous such that there are parasagittal stripes of Purkinje cells that have high expression (ZII+) alternating with stripes of Purkinje cells with low expression (ZII-). A functional zone spans a ZII+/- stripe pair. That is, each zone that contains Purkinje cells responsive to a particular pattern of optic flow is subdivided into a strip containing ZII+ Purkinje cells and a strip containing ZII- Purkinje cells. Additionally, there is optic flow input to folia VI-VIII of the cerebellum from lentiformis mesencephali. These folia also receive visual input from the tectofugal system via pontine nuclei. As the tectofugal system is involved in the analysis of local motion, there is integration of optic flow and local motion information in VI-VIII. This part of the cerebellum may be important for moving through a cluttered environment.